1991
DOI: 10.1002/mc.2940040311
|View full text |Cite
|
Sign up to set email alerts
|

Morphological transformation of 10T1/2 mouse embryo cells can be initiated by DNA double‐strand breaks alone

Abstract: Malignant transformation of mouse fibroblasts was produced by electroporation with restriction enzymes. Similar transformation frequencies were observed with Pstl, Pvull, and Xbal, which cut genomic DNA at similar overall frequencies but have different termini, i.e., a 3' overhang, a blunt end, and a 5' overhang, respectively. The dose-response curve for restriction enzyme transformation shows a marked plateau in frequencies of transformed foci per surviving cell, whereas x-irradiation of the same cells gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Low folate intake can also cause misincorporation of uracil during DNA synthesis [66, 67], potentially leading to DNA double-strand breaks [68], which in turn cause chromosome aberrations and neoplastic transformation [69]. Blount et al [70] demonstrated that both uracil mis-incorporation into DNA and high micronucleus frequency (a measure of chromosome breaks) in white blood cells from folate-deficient persons were markedly reduced after 8 weeks of folate supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Low folate intake can also cause misincorporation of uracil during DNA synthesis [66, 67], potentially leading to DNA double-strand breaks [68], which in turn cause chromosome aberrations and neoplastic transformation [69]. Blount et al [70] demonstrated that both uracil mis-incorporation into DNA and high micronucleus frequency (a measure of chromosome breaks) in white blood cells from folate-deficient persons were markedly reduced after 8 weeks of folate supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…When genomic DNA strand breaks have been generated by the introduction of restriction endonucleases into cells, a strikingly increased frequency of chromosomal aberrations has been observed in cells reaching mitosis (6,7). In addition, restriction enzymeinduced strand breaks have been found to increase neoplastic transformation (5,8,68). Finally, unrepaired or irreparable DNA strand breaks may trigger cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Folate deficiency has been observed to induce double strand breaks (DSBs) both at the genomic level and within a highly conserved area (exons 5-8) of the p53 tumor suppressor gene (19,36). Because DSBs are associated with neoplastic transformation (37) and the p53 gene is the most frequently implicated gene in colorectal carcinogenesis (38). Genomic or gene specific DNA strand breaks, or both, may be a mechanism by which folate reduction increases colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%